Implemented models and perspectives of managing lipid metabolism disorders. Concept of rare lipid disease centers - A. S. Alieva; O. V. Reutova; E. I. Pavlyuk; D. V. Duplyakov; A. V. Khripun; I. P. Efimova; Yu. A. Guryanova; E. S. Timoshchenko; A. A. Nekrasov; A. M. Namitokov; V. K. Zafiraki; E. D. Kosmacheva; et al. (Российский кардиологический журнал)
Despite the advances in lipidology over the past decade, the control of dyslipidemia at the population level in Russia, as in a number of European countries, remains unsatisfactory. The need for novel organizational approaches to solving the problem at the regional and federal levels is obvious. This publication provides an overview of the implemented projects and the successful practical experience of lipid centers in Russia, as well as the prospects for the development of novel models that will optimize the care provision for patients with lipid metabolism disorders at the population level.